Radiotherapy Response in Microsatellite Instability Related Rectal Cancer - Shin, Joo-Shik (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2013)
Preoperative radiotherapy may improve the resectability and subsequent local control of rectal cancers. However, the extent of radiation induced regression in these tumours varies widely between individuals. To date no reliable predictive marker of radiation sensitivity in rectal cancer has been identified. At the cellular level, radiation injury initiates a complex molecular network of DNA damage response (DDR) pathways that leads to cell cycle arrest, attempts at re-constituting the damaged DNA and should this fail, then apoptosis. This review presents the details which suggest the roles of DNA mismatch repair proteins, the lack of which define a distinct subset of colorectal cancers with microsatellite instability (MSI), in the DDR pathways. Hence routine assessment of the MSI status in rectal cancers may potentially serve as a predictor of radiotherapy response, thereby improving patient stratification in the administration of this otherwise toxic treatment.